Ionic and Amino Acid Regulation in Hard Clam (Meretrix lusoria) in Response to Salinity Challenges - Lin, Chia-Hao; Yeh, Po-Ling; Lee, Tsung-Han (Frontiers in Physiology, 2016)
Most marine mollusks are osmoconformers, in that, their body fluid osmolality changes in the direction of the change in environmental salinity. Marine mollusks exhibit a number of osmoregulatory mechanisms to cope with either hypo- or hyperosmotic stress. The effects of changes in salinity on the osmoregulatory mechanisms of the hard clam (Meretrix lusoria, an economically important species of marine bivalve for Taiwan) have not been determined. In this study, we examined the effect of exposure to hypo (10‰)- and hyper (35‰)-osmotic salinity on hard clams raised at their natural salinity (20‰). The osmolality, [Na+], and [Cl-] of the hard clam hemolymph were changed in the same direction as the surrounding salinity. Further, the contents of total free amino acids including taurine in the gills and mantles were significantly upregulated in hard clam with increasing salinity. The gill Na+,K+-ATPase (NKA) activity, the important enzyme regulating cellular inorganic ions, was not affected by the changed salinity. Mantle NKA activity, however, was stimulated in the 35‰ SW treatment. The taurine transporter (TAUT) is related to the regulation of intracellular contents of taurine, the dominant osmolyte. Herein, a TAUT gene of hard clam was cloned and a TAUT antibody was derived for the immunoblotting. The TAUT mRNA expression of the mantle in hard clam was significantly stimulated in 35‰ SW, but protein expression was not modulated by the changed salinity. In gills of the hard clam with 10‰ SW, both TAUT mRNA and protein expressions were significantly stimulated, and it may reflect a feedback regulation from the decreased gills taurine content under long-term hypoosmotic acclimation. These findings suggest that TAUT expression is regulated differently in gills and mantles following exposure to alterations in environmental salinity. Taken together, this study used the physiological, biochemical and molecular approaches to simultaneously explore the osmoregulation in tissues of hard clam and may further help to understand the osmoregulation in bivalves.